PENGARUH QUANTUM TEACHING TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PESERTA DIDIK DI KELAS V SEKOLAH DASAR - Kabang, Nobertha (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this reasearch is to analyze effect of the application of model quantum teaching student learning outcomes in pendidikan keawrganegaraan in 5th grade SDN 37 Southeastern Pontianak. Research method Â that used is experimental method with Quasi Experimental Design, with Nonequivalent Control Group Design. Research population is all of 5th grade of two classes from class VA to class VB with total 44 students. The sample of this research are class VA consist of 19 students (experiment) and class VB consist of 19 students (control). The average learning outcomes of final test class VA is 84,10 and class VB is 76,60 gained tarithmetic (2,195)>ttable Î±=5% (1,684), then Ha acceptable. So, the conclution is there are two average significant differences learning outcomes of students, among students group that teach with apply without method of quantum teaching and students group that teach with apply of quantum teaching approach of 5th grade in SDN 37 Southeastern Pontianak. The value of effect size is 0,49 with are criteria medium, this case mean applying model quantum teaching approach to pendidikan kewarganegaraan give are effect for learning outcomes of 5th grade in SDN 37 Southeastern Pontianak. Keywords : Quantum Teaching, Learning Outcomes